The Interest of a Systematic Toxicological Analysis Combined with Forensic Advice to Improve the Judicial Investigation and Final Judgment in Drug Facilitated Sexual Assault Cases - Sarah M. R. Wille; Karolien Van Dijck; Antje Van Assche; Vincent Di Fazio; Maria del Mar Ramiréz-Fernandéz; Vanessa Vanvooren; Nele Samyn (MDPI AG, 2021)
The conviction rate in drug facilitated sexual assault (DFSA) cases is known to be very low. In addition, the potential impact of toxicological results on the case is often not well understood by the judicial authorities. The aims of this study were (1) to obtain more knowledge concerning the prevalence of incapacitating substances in DFSA cases, (2) to create a more efficient DFSA analysis strategy taking background information into account, and (3) to evaluate the potential impact of systematic toxicological analysis (STA) on the final judicial outcome. This small-scale epidemiological study (n = 79) demonstrates that 'commonly-used' illicit drugs, psychoactive medicines and ethanol are more prevalent in DFSA cases in contrast to the highly mediatized date rape drugs. Additionally, via case examples, the interest of performing STA-to prove incapacitation of the victim-in judicial procedures with mutual-consent discussions has been demonstrated as it led to increased convictions. However, more attention has to be paid to ensure a short sampling delay and to get more accurate information from the medical treatment of the alleged victim. This will improve the interpretation of the toxicological analysis and thus its applicability in a DFSA case. The future is multi-disciplinary and will certainly lead to an efficient and more cost-effective DFSA approach in which STA can impact the final judgment.